IDDF2019-ABS-0220 Long-term outcomes of utilizing extended criteria deceased donors in liver transplantation – an australian 12-year cohort study. (June 2019) - Pandya, Keval; Sastry, Vinay; Panlilio, Mara; West, Claire; Virtue, Susan; Wells, Mark; Crawford, Michael; Pulitano, Carlo; Strasser, Simone; McCaughan, Geoff; Majumdar, Avik; Liu, Ken
Abstract : Background: The need for liver transplantation (LT) is increasing worldwide; however, organ shortage presents a major limitation. Use of extended criteria donors (ECDs) has been one strategy to increase the donor pool. Long-term outcomes in recipients of ECD livers have not been well studied. We studied the characteristics, utilization and recipient outcomes of ECDs. Methods: We retrospectively studied consecutive adults who underwent deceased LT between 2006–2018. Donor and recipient data at LT and recipient outcomes were collected from a prospective database. ECD was defined using Eurotransplant criteria as any of these donor characteristics: age >65years, ventilation >7days, BMI >30 kg/m2, liver steatosis >40%, sodium >165 mmol/L, ALT >105 U/L or AST >90 U/L, and bilirubin >51 umol/L. The primary outcome of interest was graft survival (time to retransplantation or death). Results: During the study period (median follow-up 50.6 months), 739 donors were utilized for LT. Of these, 432 (58.4%) were ECDs. Corresponding to the definition, ECDs were older (51vs.47years), with higher BMI (26.4vs.24.5 kg/m 2 ), transaminases (ALT 42vs.24 U/L) and graft steatosis (11.4%vs.0% ≥S2) compared to non-ECDs (median values, all P <0.001). ECDs also had a worse renal function (creatinine 80vs.67 umol/L, P <0.001) and a higher donor risk index (Feng et al. 2006) (1.65vs.1.52, P <0.001). There were no differences in recipient characteristics of ECD vs. non-ECD grafts except ECD recipients were less likely receive split grafts (10.9%vs.18.9%, P =0.002). The proportion of ECDs among utilized grafts did not change over time. 157 patients experienced graft loss during follow-up (31 retransplants, 126 deaths). ECDs had similar long-term graft survival compared to non-ECDs, although outcomes appeared to be worse when ≥3 criteria were met (figure 1A-B ). No individual ECD criteria were predictive for poorer graft survival. Among patients transplanted for HCC, ECD vs. non-ECD grafts resulted in similar recurrence-free survival (figure 1C ). Conclusions: ECD livers meeting up to 2 Eurotransplant criteria can be safely used without impacting long-term graft survival. This has implications for organ utilization.